Transformation of the Combinatorial Research Paradigm: A Review of the Literature and Its Application in Education - Raziska Ibrahimi; Tria Marvida; Raudha Meutia (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The development of social problems in society and the world of education is increasingly complex. One way to unravel the existing problems is to use research. One of the studies that can be used is mixed research (Combination). In a research, a combination of theory and research methodology is needed so that research objectives are created, namely positive contribution, namely solving problems faced by the research object. The type of research used is a literature study. The data collection technique in this study is by documentation. Data collection techniques are carried out in several stages, namely: 1) Identification of data sources, 2) Literature collection, 3) Literature review and synthesis. The data analysis technique used is content analysis. The results of the study explain that combination research is a research that combines and correlates qualitative and quantitative forms. The combination method consists of sequential, concurrent and transformative mixed methods. The concurrent transformative method in the design of the mixed research method is one part of the mixed research method.